Effect of role overload, budget participation, environmental uncertainty, organizational culture, competence, and compensation on employee performance - Prihantari, Gusti Ayu Putu Eka Dewi; Astika, Ida Bagus Putra (International research journal of management, IT and social sciences, 2019)
The purpose of this study was to obtain empirical evidence of the effect of role overload, budgetary participation, environmental uncertainty, organizational culture, competence, and compensation on employee performance. The population in this study were all employees of PT. Tatamulia Nusantara Indah. The method of determining the sample used in this study is the saturated sample method. Saturated sample method is a sampling technique if all members of the population are used as samples so that the number of respondents in this study is 90 respondents. The data used in the form of primary data using a questionnaire. The analysis technique used is multiple linear regression. The results showed that role overload negatively affected employee performance, budgeting participation had a positive effect on employee performance, environmental uncertainty had a negative effect on employee performance, organizational culture had a positive effect on employee performance, competency had a positive effect on employee performance, and compensation had a positive effect on employee performance at PT. Tatamulia Nusantara Indah.